Answer:
Step A : -2.5(0.5 - 2.5x - 2.5) + 2.5(-4x -1) = -2x - 4 x
Given, is used in "given this equation"
Step B: -5 (1- 5) + 5( -8x - 2) = -4x - 8x
Here you can see like they multiplication both sides of the equation by 2.
2*( -2.5(0.5 - 2.5x - 2.5) + 2.5(-4x -1)) = 2*(-2x - 4 x)
-5(0.5 - 2.5x - 2.5) + 5(-4x -1) = -4x - 8 x
Looks like your teacher also multiplied by two inside the parentheses, which is a mistake, but we will keep progressing with the expressions in the image.
So the option here is multiplication property of equality.
Step C: Here you are solving the parentheses, this is the distributive property.
Step D: Now you are writing a equivalent equation, in this step you have:
-5 + 25x -40x - 10 = -4x - 12x
(-5 - 10) + (25x - 40x) = -12x
-15 - 15x = -12x
Step E: Here you are adding 15x in both sides of the equation, you are using the addition property of equality.
Step F: now you are dividing both sides by 3, this is the division property of equality.